2005
DOI: 10.1007/s10549-005-6653-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Breast Cancer Tumor Size Depends on Method, Histopathology and Tumor Size Itself*

Abstract: The dimension of invasive ductal carcinomas, small and low grading tumors is significantly better to estimate. Concerning treatment decisions, we propose a combination of all three modalities, as the best predictive value was seen for the complementary use of mammography, ultrasound and clinical examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 22 publications
(35 reference statements)
7
50
1
1
Order By: Relevance
“…These Physical exploration results are congruent with other studies published in the literature (6)(7)(8)(9)12,13). Breast density had a negative influence on the sensitivity of mammography, with sensitivity of 30-48% in very dense breast (10,(14)(15)(16). Our study compares the three techniques in all patients, we do not use analogic or digital MM, we use Mammography3D tomosynthesis, maybe can explain why we visualized the tumor by MM in all of our patients independently of mammary density, since in other studies MM does not always visualize the tumor when using analogic or digital MM (5,6,12,(15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These Physical exploration results are congruent with other studies published in the literature (6)(7)(8)(9)12,13). Breast density had a negative influence on the sensitivity of mammography, with sensitivity of 30-48% in very dense breast (10,(14)(15)(16). Our study compares the three techniques in all patients, we do not use analogic or digital MM, we use Mammography3D tomosynthesis, maybe can explain why we visualized the tumor by MM in all of our patients independently of mammary density, since in other studies MM does not always visualize the tumor when using analogic or digital MM (5,6,12,(15)(16)(17).…”
Section: Discussionsupporting
confidence: 89%
“…Breast density had a negative influence on the sensitivity of mammography, with sensitivity of 30-48% in very dense breast (10,(14)(15)(16). Our study compares the three techniques in all patients, we do not use analogic or digital MM, we use Mammography3D tomosynthesis, maybe can explain why we visualized the tumor by MM in all of our patients independently of mammary density, since in other studies MM does not always visualize the tumor when using analogic or digital MM (5,6,12,(15)(16)(17). However, mammography continues to be a gold standard test, since it allows visualization of lesions such as microcalcifications or in situ carcinoma, in which US has a low utility.…”
Section: Discussionmentioning
confidence: 99%
“…There may be a considerable difference between the estimated tumour sizes pre-operatively and after histological examination (1,10,11). …”
Section: Introductionmentioning
confidence: 99%
“…Tumour size is usually assessed using a clinical examination, mammography, ultrasound and magnetic resonance imaging of the breast, or combinations of these methods [6][7][8][9]. Mammographic and ultrasound assessment of tumour size have been described previously elsewhere.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies advocate using ultrasound as the preferred method of predicting the real histopathological tumour size, although most studies have found that ultrasound underestimates the size of breast lesions [6,8,10]. However, the published studies [6,8,[10][11][12][13][14][15][16] may not reflect current technical standards in mammography and ultrasound, as compound imaging and real-time elastography in particular, as a quite new technique in breast diagnosis, may now allow more accurate tumour size estimation [17][18][19][20][21][22][23][24]. Elastography is able to image the elasticity of soft tissues [21].…”
Section: Introductionmentioning
confidence: 99%